2014
DOI: 10.5539/ibr.v7n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corruption on Foreign Direct Investment in Africa

Abstract: A new area of research has recently emerged that analyzes the impact of corruption on foreign direct investment (FDI) in developing countries. The FDI literature comprises two opposing views of corruption-the grabbing hand hypothesis holds that corruption impedes FDI by raising uncertainty and transaction costs and the helping hand hypothesis holds that corruption facilitates FDI by greasing the wheels of commerce in the presence of weak regulatory frameworks. This study analyzes the impact of corruption on FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 35 publications
(35 reference statements)
9
43
1
Order By: Relevance
“…Foreign direct investment (FDI) is also defined as an investment in equity with a least verge of 10% beside an ownership intention and long-term management interest (Hasan, Rahman & Iqbal, 2017). FDI fills three gaps in developing countries which includes: provision of funds for investment, availability of foreign currency and generation of tax revenues for the government (Quazi, Vemuri & Soliman, 2014). The recent negative FDI trend got the entire global investment community worried as to what could be the major cause of the sharp decline of FDI by 23% in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign direct investment (FDI) is also defined as an investment in equity with a least verge of 10% beside an ownership intention and long-term management interest (Hasan, Rahman & Iqbal, 2017). FDI fills three gaps in developing countries which includes: provision of funds for investment, availability of foreign currency and generation of tax revenues for the government (Quazi, Vemuri & Soliman, 2014). The recent negative FDI trend got the entire global investment community worried as to what could be the major cause of the sharp decline of FDI by 23% in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…This simply means that the more countries are perceived to be corrupt among other countries, the less easy is to start businesses in such countries, while the higher the perception score and control of corruption a country has, the easier doing business in such countries. This fi nding is in tandem with the fi ndings of Mongay and Filipescu (2012), Nageri, Nageri, and Amin (2015), Bounoua and Matallah (2014), and Omodero (2019) but in disagreement with the fi ndings of Gutierrez (2015), Quazi et al (2014), and Bayar and Alakbarov (2016).…”
Section: Table 5 Hausman Test Results For Corruption Rankmentioning
confidence: 72%
“…Their examination demonstrated that the least corrupt countries attracted more FDI since they were deemed investor friendly. However, Quazi et al (2014) investigated the effect of corruption on FDI on 53 African countries for the period 1995 to 2012 and indicated that corruption had the greasing effect on investors entering the African market. Barassi and Zhou (2012) aver that corruption reduces the probability of FDI by 3 percent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Findings on the impact of corruption on FDI are inconsistent. Some studies suggest corruption deters FDI inflows (Dridi, 2013;Faruq et al, 2013;Heywood and Rose, 2014) and others suggest a positive relationship (Quazi et al, 2014). Zimbabwe is one of the countries with the highest corruption according to Transparent International Perception of Corruption Index.…”
Section: Justification Of the Variablesmentioning
confidence: 99%